Chemoradiotherapy but not radiotherapy alone for larynx preservation in T3: considerations from a German observational cohort study - Dyckhoff, Gerhard; Warta, Rolf; Herold-Mende, Christel; Winkler, Volker; Plinkert, Peter K.; Ramroth, Heribert (Cancers, 2021)
For advanced laryngeal cancers, after randomized prospective larynx preservation studies, nonsurgical therapy has been applied on a large scale as an alternative to laryngectomy. For T4 laryngeal cancer, poorer survival has been reported after nonsurgical treatment. Is there a need to fear worse survival also in T3 tumors? The outcomes of 121 T3 cancers treated with pCRT, pRT alone, or surgery were evaluated in an observational cohort study in Germany. In a multivariate Cox regression of the T3 subgroup, no survival difference was noted between pCRT and total laryngectomy with risk-adopted adjuvant (chemo)radiotherapy (TL ± a(C)RT) (HR 1.20; 95%-CI: 0.57-2.53; p = 0.63). However, survival was significantly worse after pRT alone than after TL ± a(C)RT (HR 4.40; 95%-CI: 1.72-11.28, p = 0.002). A literature search shows that in cases of unfavorable prognostic markers (bulky tumors of 6-12 ccm, vocal cord fixation, minimal cartilage infiltration, or N2-3), pCRT instead of pRT is indicated. In cases of pretreatment dysphagia or aspiration requiring a feeding tube or tracheostomy, gross or multiple cartilage infiltration, or tumor volume > 12 ccm, outcomes after pCRT were significantly worse than those after TL. In these cases, and in cases where pCRT is indicated but the patient is not suitable for the addition of chemotherapy, upfront total laryngectomy with stage-appropriate aRT is recommended even in T3 laryngeal cancers.